Multi-dimensional Data Visualisation using Mobile Augmented Reality - Rehman Ullah, Khan; Yin, Bee Oon; Ahmad Sofian, Shminan; Lee, Jun Choi; Chen, Jacqueline How Ting (IJICC, 2020)
In the era of “The Internet of Things” (Rodriguez, Kaczmarek, & Depew) devices are becoming smart and each smart device generates data every second. This data is in multi-format, multi-perspective and multi-sectoral. Therefore, the handling of such multi-dimensional data is a significant challenge, as the normal display screen is two dimensional (2D) and data is multi-dimensional. This research proposes and develops a multi-display data visualisation algorithm using mobile augmented reality, as augmented reality (AR) is beyond the two-dimensional screen. Therefore, this algorithm uses AR to provide a multi-display solution for improved data visualisation after processing, summarising and classifying data. The results show that the AR-based multi-display is better than traditional 2D display. This algorithm is mobile based. Therefore, this system can provide rapid and easily accessible information to policy and decision makers.